Managing virtual rapport on tripadvisor: discourse in hotel responses to negative online reviews - Taw, Ly Wen; Paramasivam, Shamala; Libert, Alan; Moskovsky, Christo; Jalaluddin, Ilyana; Darmi, Ramiza (Penerbit Universiti Kebangsaan Malaysia, 2022)
Digital technology has immensely transformed communication, and social media facilitates online feedback mechanisms, empowering consumers' voices via online reviews. This has led to the pervasively growing influence of electronic word of mouth (eWOM) on customers' purchase intentions, as negative online reviews can be detrimental to business performance. Therefore, digital business engagement on online platforms is essential to ensure customer satisfaction and manage online reputation. Building on Spencer-Oatey's (2008) Rapport Management Model (RMM), this qualitative study explores the rapport management strategies used by eighteen Malaysian five-, four- and three-star hotels to respond to negative online reviews, from the perspective of the RMM discourse domain. The hotel responses were collected from TripAdvisor, using purposeful sampling and analysed with Computer-Mediated Discourse Analysis. The findings show that the five- and four-star hotels employed higher frequencies of moves in their responses to complaints in negative reviews. Some four- and three-star hotels took a more confrontational approach by using the sub-move 'denying problems'. In terms of RMM rapport orientation, this sub-move can be rapport-challenging in customer relationships. This study highlights that managing negative reviews more efficiently for service recovery on online platforms is essential to maintain customer relationships and establish a positive online corporate reputation. More generally, the findings provide insights on cultural rapport management strategies used in one Southeast Asian country-Malaysia.